A paper fortune teller-inspired reconfigurable soft pneumatic gripper. (19th February 2021) - Chen, Rui; Zhang, Chen; Sun, Yi; Yu, Tao; Shen, Xin-Ming; Yuan, Ze-An; Guo, Jiang-Long
Abstract: Soft pneumatic grippers (SPGs) have shown great grasping performances for various objects due to their simplicity, adaptability and rapid response. However, there are few SPGs that can grasp both flat and non-planar targets robustly. A reconfigurable mechanism that can transform the gripper into different states for grasping varied objects is desired by such versatile SPGs. Paper fortune teller (PFT) is a distinctive origami with 2D/3D shape switchability and 3D shape reconfigurability. In this paper, we propose a novel reconfigurable SPG which is inspired from PFT and augmented with an indirect vacuum adhesion (IVA) mechanism. The resultant gripper can not only lift flat-surface objects such as a piece of square glass (278 g) with the IVA force in its pad shape, but also pick up non-planar objects such as an orange (151 g) in a traditional grasping way in its four-converging-fingered shape. The experimental results reveal that our gripper can produce a maximum IVA force of about 4.24 N on acrylic plates and a maximum pulling force of about 2.10 N on 3D-printed non-planar objects respectively. The gripper's traditional grasping robustness is also demonstrated when non-planar objects are placed irregularly (allowing up to 55 mm multi-orientation offsets or 20° multi-orientation drift angles). This new SPG design realizes the multi-function nature of origami transformation and is expected to promote the application of origami and soft gripper technologies.